Mykola V. answered • 12/06/12

Math Tutor - Patient and Experienced

Let's first split this expression into two parts. We have the (2h)^{7} and 7h. We need to simplify the (2h)^{7} before we can combine them.

(2h)^{7} = 2^{7}*h^{7}=128*h^{7}=128h^{7. }In this step the exponent can be distrubed into the parenthese to each individual term.

We can now combine the 7h with what we got in the previous step:

128h^{7}*7h=128*7*h^{7}*h=896h^{8}. As per law of exponents: x^{m}*x^{n}=x^{m+n}.

Hope this helps.